Pengaruh Komposisi Campuran Serbuk Batang Singkong dan Serai Wangi terhadap Kualitas Obat Nyamuk Bakar - Dahlia Dahlia; Sandi Asmara; Muhammad Amin; Sapto Kuncoro (Jurnal Agricultural Biosystem Engineering, 2022)
Mosquito repellent are drugs used to repel or kill mosquitoes. Eco-friendly mosquito repellent or vegetable mosquito repellent can be made from various types of vegetable raw materials that contain mosquito-killer / repellent compounds such as cassava stem powder waste and citronella.  This cassava stem waste is very potential to be used because it is being one of the environmental problems in Indonesia. This research aims to establish the formation of mosquito repellent made from cassava stem powder and citronella, determine the suitability of quality based on the specifications of mosquito coils produced against SII No.1113-84 and organoleptic testing of mosquito coils. This research was conducted using a completely randomized design (CRD) with five treatments and three replications. The experiment consisted of 5 levels of mixed composition, namely 30% cassava stalks: 70% citronella (P1), 40% cassava stalks 60% lemongrass fragrant (P2), 50% cassava stalks: 50% citronella (P3), 60% cassava stalks.  40% citronella (P4), and 70% cassava stalks: 30% lemongrass (P5). The results showed that the mosquito repellent formed had a circle dimension of 81 cm, a diameter of 12 cm, a light brown color, a width of 7 mm, and a thickness of 4 mm. The quality of mosquito repellent based on the specifications is as follows: the moisture content range from 5.36 - 9.41% which fulfill the 80% quality standard, the burning time range from 3 - 4 hours, and the weight per seed range from 9.35 - 9, 77 grams. Judging from the quality based on these specifications, the mosquito repellent that is made does not fulfill the quality based on the specifications and quality requirements of SII. However, the mosquito repellent made is suitable for use as natural mosquito repellent because it is close to SII. Meanwhile, based on the organoleptic test with aroma parameters, the best natural mosquito repellent are treatment 1, formed by a mixture of 30% cassava stalks and 70% citronella.  Panelists gave an average score of 4.7 with the criteria being fragrant to very fragrant. Keywods: Cassava Stem Powder, Citronella Powder, Mosquito Repellent.